“Two-zone and Three-segment” Laparoscopic Radical Cystectomy vs Conventional Laparoscopic Radical Cystectomy for Male Patients With Bladder Urothelial Carcinoma: A Retrospective Analysis - Chen, Shouzhen; Cui, Jianfeng; Sun, Haoyu; Wang, Wenfu; Liu, Xigao; Zhang, Dongqing; Jiang, Xianzhou; Guo, Hu; Xing, Nianzeng; Zhu, Yaofeng; Shi, Benkang (Urology Journal, 2022)
Purpose: The aim of this study was to introduce an advanced surgical technique for laparoscopic radical cystectomy (LRC), evaluate the perioperative outcome and compare it to that of conventional LRC (CLRC). Materials and Methods: Between March 2018 and March 2020, sixty patients were divided into the “two-zone and three-segment” laparoscopic radical cystectomy (TTLRC) group or the CLRC group. Patient baseline characteristics, preoperative characteristics and postoperative complications were collected. Results: The TTLRC technique was developed based on the pelvic anatomy of six formalin fixed male cadavers. None of the patient baseline characteristics, including ECOG-PS score, comorbidity, ASA score and Hb, were significantly different between the two groups (p>0.05). There were significant differences in the operating time and estimated blood loss (total time: 3±0.2 vs 3.8±0.4, p<0.001; time to cystectomy and lymph node dissection: 1.7±0.2 vs 2.2±0.3, p<0.001; estimated blood loss 182.1±18.8 vs 264.3±27.4, p<0.001). Although there were no differences in late complications, early complications were significantly different between the two groups (p = 0.033). No statistically significant differences were found between the two groups in other outcomes (p>0.05). Conclusion: The TTLRC technique achieves a clearer surgical field, has a shorter operating time and produces less blood loss than CLRC. It is safe and feasible for urologists to perform this improved LRC procedure.